Laberintos y metamorfosis: Estéticas en tensión en Jorge Luis Borges y Silvina Ocampo - García, Mariano (Amaltea. Revista de Mitocrítica, 2009)
We propose in this study the confrontation of two mythemes that, following Foucault, articulate Occidental fabulation: the labyrinth and the metamorphosis, in order to demonstrate that the inclination for one or the other determinates a particular esthetic. For doing so, we will take Jorge Luis Borges’ and Silvina Ocampo’s works, though we will only carry out an exhaustive analysis of Ocampo’s work with structuralist and deconstructive tools, as well as some mythocritic elements.
Keywords: Labyrinth; Metamorphosis; Silvina Ocampo